Health Behaviors and All-Cause Mortality in African American Men - Thorpe, Roland J. (2013)
Because of the excess burden of preventable chronic diseases and premature death among African American men, identifying health behaviors to enhance longevity is needed. We used data from the Third National Health and Nutrition Examination Survey 1988-1994 (NHANES III) and the NHANES III Linked Mortality Public-use File to determine the association between health behaviors and all-cause mortality and if these behaviors varied by age in 2029 African American men. Health behaviors included smoking, drinking, physical inactivity, obesity, and a healthy eating index score. Age was categorized as 25-44 years (n = 1,045), 45-64 years (n = 544), and 65 years and older (n = 440). Cox regression analyses were used to estimate the relationship between health behaviors and mortality within each age-group. All models were adjusted for marital status, education, poverty-to-income ratio, insurance status, and number of health conditions. Being a current smoker was associated with an increased risk of mortality in the 25- to 44-year age-group, whereas being physically inactive was associated with an increased risk of mortality in the 45- to 64-year age-group. For the 65 years and older age-group, being overweight or obese was associated with decreased mortality risk. Efforts to improve longevity should focus on developing age-tailored health promoting strategies and interventions aimed at smoking cessation and increasing physical activity in young and middle-aged African American men.